THE EFFECT OF CULTURAL AND ENVIRONMENTAL CONDITIONS ONBIODEGRADATION AND BIOSURFACTANT PRODUCTION BYSERRATIA MARCESCENS UTILIZING WEATHERED DIESEL OIL - Gumaa, Nadem H Hayder; Potrus, Wameidh M; Mohammed, Sahar Imad (Al-Nahrain Journal of Science, 2010)
The capability of a Serratia marcescens isolate to biosurfactant production from spilled weathered diesel oil has been studied in batch culture. Several cultural and environmental conditions were analyzed to optimized condition for growth and biosurfactant production. Results showed that the optimized conditions which for growth was, pH 7, incubation period for 72 h, supplementation of the production medium with (NH4)2 SO4 0.4 % and weathered diesel oil in a concentration of 5 % which yielded 8.6 g/l biomass. Optimized condition for biosurfactant production was, pH 8, incubation period 96 h, (NH4)2 SO4 0.2 % and weathered diesel oil in a concentration of 6 % which yielded 10.5 g/l biosurfactant. Temperature 30 C was optimum for growth and biosurfactant production. Surface active properties of isolate studied during cultivation with weathered diesel oil at the concentration 6 % (w/v) at different incubation period. The isolate has synthesized extra cellular compounds which increase the E 24 % emulsion index of culture medium to 58 % and emulsification activity to 0.9. The presence of these substances (crude form) lower the surface tension of the culture until 43 mN/m. Bacterial cell surface hydrophobicity (BAH) as measured by analyzing cell affinity towards aliphatic, aromatic and mixed hydrocarbons was also determined. The isolate was found to have a surface hydrophobicity (Hydrocarbon affinity) in the following order: aliphatic, mixed and monoaromatic hydrocarbons. The present study concludes possibility of using surface active agents (Biosurfactant) produced by Serratiamarcescens mainly in: petroleum industry in enhanced oil recovery and in variety of biotechnological applications, including bioremediation of hydrocarbons contaminated sites.